Discovery of Oral VEGFR-2 Inhibitors with Prolonged Ocular Retention That Are Efficacious in Models of Wet Age-Related Macular Degeneration - Meredith, Erik L. (2016)
The benefit of intravitreal anti-VEGF therapy in treating wet age-related macular degeneration (AMD) is well established. Identification of VEGFR-2 inhibitors with optimal ADME properties for an ocular indication provides opportunities for dosing routes beyond intravitreal injection. We employed a high–throughput in vivo screening strategy with rodent models of choroidal neovascularization and iterative compound design to identify VEGFR-2 inhibitors with potential to benefit wet AMD patients. These compounds demonstrate preferential ocular tissue distribution and efficacy after oral administration while minimizing systemic exposure.